Happy to Help: Welfare Effects of a Nationwide Volunteering Programme - Krekel, Christian; Shreedhar, Ganga; Lee, Helen; Marshall, Claire; Boler, Alison; Smith, Allison; Dolan, Paul (The Review of Economics and Statistics, 2024)
Abstract We study the wellbeing returns from volunteering in England's National Health Service (NHS) Volunteer Responders, set up in response to Covid-19. Using linked survey and administrative data, we exploit the oversubscription of volunteers and the random allocation of tasks via an app to establish causality. Volunteers show stronger wellbeing and feelings of belongingness and connectedness to their local area. Welfare analyses suggest that the benefits of the programme substantially exceeded its costs. We are the first to study the welfare effects of a nationwide volunteering programme. Our findings show that pro-social behaviour improves personal wellbeing as well as social welfare.